Mengukir Kesadaran Lingkungan: Sinergi Kebijakan dan Transformasi Perilaku Menuju Kampus Hijau Universitas Islam Negeri Raden Intan Lampung - Ika Wulan Handayani (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This study analyzes the low awareness and participation of UIN Raden Intan Lampung's academic community in sustainable green campus implementation, despite the institution's strong commitment and impressive UI GreenMetric achievements. This phenomenon is paradoxical, marked by increased energy consumption and vehicle ratios, indicating a gap between infrastructure provision and expected behavioral change. The research objective is to analyze the fundamental factors contributing to low participation and formulate strategic policy alternatives that can be implemented. The research method employs a descriptive qualitative approach with extensive document review. The identification of the main problem was conducted through Urgency, Seriousness, Growth (USG) analysis, followed by root cause analysis using a Fishbone Diagram. The frameworks of Theory of Planned Behavior, Diffusion of Innovation, and Policy Implementation Theory, supported by the concept of Ecotheology, serve as a comprehensive analytical foundation. Research results indicate that 'Low Level of Awareness and Active Participation of the Academic Community' is the top priority issue (USG score 14), rooted in a lack of knowledge, suboptimal education programs, unclear participation mechanisms, and incomplete integration of environmental issues within policies and curriculum. These findings affirm systemic weaknesses rather than mere individual failures. In conclusion, this study recommends 'Comprehensive Integration of Environmental Education in Curriculum and Extracurricular Activities' as the most optimal policy alternative (score 19). The issuance of a binding Rector's Regulation to comprehensively integrate Ecotheology-based environmental education is crucial. This is expected to transform campus culture, produce environmentally conscious graduates, and position UIN as a model Islamic institution in sustainability.